Degradation of trichloroethylene by Pseudomonas cepacia G4 and the constitutive mutant strain G4 5223 PR1 in aquifer microcosms. - Krumme, M L (1993)
Pseudomonas cepacia G4 degrades trichloroethylene (TCE) via a degradation pathway for aromatic compounds which is induced by substrates such as phenol and tryptophan. P. cepacia G4 5223 PR1 (PR1) is a Tn5 insertion mutant which constitutively expresses the toluene ortho-monooxygenase responsible for TCE degradation. In groundwater microcosms, phenol-induced strain G4 and noninduced strain PR1 degraded TCE (20 and 50 microM) to nondetectable levels (< 0.1 microM) within 24 h at densities of 10(8) cells per ml; at lower densities, degradation of TCE was not observed after 48 h. In aquifer sediment microcosms, TCE was reduced from 60 to < 0.1 microM within 24 h at 5 x 10(8) PR1 organisms per g (wet weight) of sediment and from 60 to 26 microM over a period of 10 weeks at 5 x 10(7) PR1 organisms per g. Viable G4 and PR1 cells decreased from approximately 10(7) to 10(4) per g over the 10-week period.